“Daring to Care”: Challenging Corporate Environmentalism - Phillips, Mary (Journal of business ethics, 2019)
Corporate engagements with pressing environmental challenges focus on expanding the role of the market, seeking opportunities for growth and developing technologies to manage better environmental resources. Such approaches have proved ineffective. I suggest that a lack of meaningful response to ecological degradation and climate change is inevitable within a capitalist system underpinned by a logics of appropriation and an instrumental rationality that views the planet as a means to achieve economic ends. For ecofeminism, these logics are promulgated through sets of hierarchical and interrelated dualisms which define the human in opposition to the realm of “nature”. This has led to the resilience of ecosystems, social reciprocity and care being unvalued or undervalued. An ecofeminist, care-sensitive ethics is proposed that focuses on the interconnections between human and nonhuman nature and on affective engagements with the living world. A practical morality is developed that sees the self not as atomized nor as self-optimizing, but as a self in relationship. Such an ethics is necessary to motivate action to contest capitalism’s binary thinking, evident within corporate environmentalism, which has re-made the web of life in ways that are not conducive to planetary flourishing.